Ritonavir inhibits intratumoral docetaxel metabolism and enhances docetaxel antitumor activity in an immunocompetent mouse breast cancer model. Issue 3 (21st September 2015) - Hendrikx, Jeroen J.M.A.; Lagas, Jurjen S.; Song, Ji‐Ying; Rosing, Hilde; Schellens, Jan H.M.; Beijnen, Jos H.; Rottenberg, Sven; Schinkel, Alfred H.
Abstract : Docetaxel (Taxotere ® ) is currently used intravenously as an anticancer agent and is primarily metabolized by Cytochrome P450 3A (CYP3A). The HIV protease inhibitor ritonavir, a strong CYP3A4 inhibitor, decreased first‐pass metabolism of orally administered docetaxel. Anticancer effects of ritonavir itself have also been described. We here aimed to test whether ritonavir co‐administration could decrease intratumoral metabolism of intravenously administered docetaxel and thus increase the antitumor activity of docetaxel in an orthotopic, immunocompetent mouse model for breast cancer. Spontaneously arising K14cre;Brca1 F/F ;p53 F/F mouse mammary tumors were orthotopically implanted in syngeneic mice lacking Cyp3a ( Cyp3a −/− ) to limit ritonavir effects on systemic docetaxel clearance. Over 3 weeks, docetaxel (20 mg/kg) was administered intravenously once weekly, with or without ritonavir (12.5 mg/kg) administered orally for 5 days per week. Untreated mice were used as control for tumor growth. Ritonavir treatment alone did not significantly affect the median time of survival (14 vs . 10 days). Median time of survival in docetaxel‐treated mice was 54 days. Ritonavir co‐treatment significantly increased this to 66 days, and substantially reduced relative average tumor size, without altering tumor histology. Concentrations of the major docetaxel metabolite M2 in tumor tissue were reduced by ritonavir co‐administration, whereas tumor RNA expression of Cyp3a was unaltered. In this breast cancer model, we observed no direct antitumor effect of ritonavir alone, but we found enhanced efficacy of docetaxel treatment when combined with ritonavir. Our data, therefore, suggest that decreased docetaxel metabolism inside the tumor as a result of Cyp3a inhibition contributes to increased antitumor activity. Abstract : What's new? The anticancer drug docetaxel is extensively metabolized by the CYP3A enzyme, the activity of which can be blocked by the protease inhibitor ritonavir. Here, in Cyp3A‐deficient mice orthotopically implanted with spontaneously arising Cyp3A‐expressing mammary tumors, tumor size was found to be significantly reduced by co‐administration of docetaxel and ritonavir. Within mammary tumors, Cyp3a inhibition by ritonavir was associated with decreased local docetaxel metabolism, which in turn increased the antitumor activity of docetaxel. Tumor histology was unchanged by the addition of ritonavir, suggesting that the drug has no direct antitumor effects.